"Never let a good crisis go to waste" - Požgan, Jure (Teorija in praksa, 2020)
In this article, we argue that while examining the Western Balkans% integration process during the Covid-19 crisis we must take into consideration not only the EU%s influence but that of other powerful external actors as well. Based on the external incentives model, Russia, China and Turkey are thus analysed as competing external actors to the EU%s enlargement policy in the WB. We establish that during the Covid-19 crisis these actors have been increasingly competing with the EU especially with respect to the determinacy of conditions via state propaganda and by attacking the EU%s credibility with disinformation campaigns. Nevertheless, their influence in terms of the size of the rewards and domestic adoption costs has dropped in comparison to the EU as the latter has increased its rewards, strengthened conditionality and regained some of its lost credibility capabilities. The most significant change visible during the Covid-19 crisis is a further fragmentation in addressing individual WB states by Russia, China and Turkey, whereas the EU remains the only external actor capable and willing to addresses the entire WB region.
Keywords: Covid-19; Članstvo; članstvo EU; Epidemics; Epidemije; evropska integracija; Evropska unija; Membership; Ozemeljska širitev; širitvena politika; Territorial expansion; Zahodni Balkan